2021
DOI: 10.1101/2021.09.20.21263753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting a History of Repetitive Head Impacts from a Short Voice Recording

Abstract: Repetitive head impacts (RHI) are associated with an increased risk of developing various neurodegenerative disorders, such as Alzheimer's disease (AD), Parkinson's disease (PD), and most notably, chronic traumatic encephalopathy (CTE). While the clinical presentation of AD and PD is well established, CTE can only be diagnosed post-mortem. Therefore, a distinction can be made between the pathologically defined CTE and RHI-related functional or structural brain changes (RHI-BC) which may result in CTE. Unfortun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Acoustic speech measures show great promise in early identification of RHI-related behavioral changes. Tauro and colleagues 13 recently differentiated speakers with and with no history of RHI with 85% accuracy using automated analysis of 13-second voice recordings, including the correct classification of boxers who were just 21 years of age. Articulation rate, pausing, and disfluencies are relatively easy to measure, even in everyday speaking conditions and by automatic recognition systems, so they have the potential for early clinical identification of RHIassociated neurological decline and to track changes in behavior over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic speech measures show great promise in early identification of RHI-related behavioral changes. Tauro and colleagues 13 recently differentiated speakers with and with no history of RHI with 85% accuracy using automated analysis of 13-second voice recordings, including the correct classification of boxers who were just 21 years of age. Articulation rate, pausing, and disfluencies are relatively easy to measure, even in everyday speaking conditions and by automatic recognition systems, so they have the potential for early clinical identification of RHIassociated neurological decline and to track changes in behavior over time.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two recent reviews discuss the utility of speech biomarkers such as speech rate, pause time, and pause duration for the detection of neurological disturbance including Parkinson disease, amyotrophic lateral sclerosis, and RHI. 11,12 For example, Tauro et al 13 reported that acoustic machine learning techniques differentiated speakers with and with no history of RHI with 85% accuracy. In this study, we compared fighters exposed to RHI with controls who had no history of RHI exposure on several characteristics of connected speech that have been associated with various types of dysarthria and that can be reliably measured in speech samples collected in clinical conditions.…”
Section: Encephalopathy (Cte) Definitive Diagnosis Of Cte Canmentioning
confidence: 99%